Factors Contributing to the Difficulty of Reading Arabic Texts Among Eighth Grade Students - Baiquni, Achmad Mukti; Adam, Faisol Mahmoud; Aziz, Abdul (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Reading ability is one of the fundamental skills in mastering the Arabic language, and it is essential for fully understanding the content of a text. However, many students face difficulties in grasping the structure, vocabulary, and meaning of the texts they read. This study aims to identify and analyze the factors that cause reading difficulties in Arabic texts among eighth-grade students at Ma’had Muhammadiyah Munawaroh Malang. A qualitative approach was used, employing a case study method. Data were collected through observation, interviews, and documentation. The results of the study show that reading difficulties are influenced by several factors: internal factors 1) Students' learning experience and language competence; 2) Vocabulary mastery; 3) Students' interest in Arabic; 4) Not used to reading Arabic texts independently; 5) Fear of making mistakes and lack of self-confidence. External Factors:1) The teacher has not yet varied their teaching methods and techniques, and 2) Study Time. These findings are expected to serve as a basis for educators to evaluate and design more effective teaching strategies to improve students’ Arabic reading skills.